The China-India rivalry in the globalization era - Paul, T. V. (South Asia in world affairs series., 2018)
This volume examines whether or not the rivalry between India and China that began in the 1950s will intensify or dissipate in the twenty-first century. The China-India relationship is important to analyze because past experience has shown that when two rising great powers share a border, the relationship is volatile and potentially dangerous. India and China have multiple border disputes that flare up; they are divided by the status of Tibet and the Dalai Lama; China's close relationship with Pakistan is a strategic challenge to India; the Chinese navy's greater presence in the Indian Ocean has made India wary, and the two states compete for natural resources. Despite these irritants, both countries also have much to gain from increasing trade and investment, so there are reasons for optimism as well as pessimism. T.V. Paul and the contributors to this volume answer the following questions: What explains the peculiar contours of this rivalry? What influence does accelerated globalization, especially increased trade and investment, have on this rivalry? What impact does the US-China competition and China's expanding navy have on this rivalry? Under what conditions will it escalate or end?